2014
DOI: 10.4025/actascianimsci.v36i4.24331
|View full text |Cite
|
Sign up to set email alerts
|

<b>Digestible lysine levels for brown layers

Abstract: ABSTRACT. This study was carried out to evaluate the effects of different digestible dietary lysine levels on performance and egg quality characteristics, from 25 to 41 weeks of age. One hundred twenty Hy-Line Brown layers were randomly distributed in five treatments with six replications of four birds each, totaling 30 experimental units. Experimental diets were based on corn and soybean meal, were isocaloric and isonutrient, with differences only in lysine levels (0.70, 0.75, 0.80, 0.85, and 0.90%). The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, earlier workers reported that dietary supplementation of lysine had no effects on egg shape index and haugh unit (Fouad et al, 2018). In contrast, no improvement in haugh unit in Hy-Line Brown laying hens and Hy-Line W-36 laying hens was reported due to dietary supplementation of lysine (da Rocha et al, 2009 andSouza et al, 2014). The value of haugh unit ranged from 92.51-97.24 in present study.…”
Section: Resultscontrasting
confidence: 72%
“…However, earlier workers reported that dietary supplementation of lysine had no effects on egg shape index and haugh unit (Fouad et al, 2018). In contrast, no improvement in haugh unit in Hy-Line Brown laying hens and Hy-Line W-36 laying hens was reported due to dietary supplementation of lysine (da Rocha et al, 2009 andSouza et al, 2014). The value of haugh unit ranged from 92.51-97.24 in present study.…”
Section: Resultscontrasting
confidence: 72%
“…The variations observed in suggested amino acid requirements (Bregendahl et al 2008 andJi et al 2014) may be due to different experimental conditions including composition of diet, types of feed ingredients (Li et al 2013), strain (Santos et al 2014), dietary energy content (Souza et al 2014), feed intake levels and age of layers. Most of the research done so far was in the environment controlled houses on corn-soya diet.…”
Section: Introductionmentioning
confidence: 98%
“…Kakhki et al (2016) reported that increasing Lys levels from 0.657% to 0.857% in Hy-Line W36 laying hens did not affect egg shape index, yolk proportion, albumen proportion, eggshell proportion, or eggshell thickness, whereas Haugh unit enhanced with elevating Lys levels in their diets, while Kumari et al (2016) found that Hugh unit, yolk colour, and eggshell thickness of WL laying hens did not alter by increasing Lys concentration in their diets. Also, in Hy-Line Brown laying hens and Hy-Line W-36 laying hens, the findings exhibited no improvements in the Haugh unit, yolk weight, yolk%, albumen weight, albumen%, eggshell weight, eggshell%, or eggshell thickness when they consumed diets supplemented with Lys (da Rocha et al 2009;Souza et al 2014), while de Carvalho et al 2015and Schmidt et al (2008) found a significant decline in eggshell percentage due to increasing Lys levels in Lohmann LSL laying hens diets, whereas yolk and albumen percentage did not change. In laying quails, Ribeiro et al (2013) recorded a significant increase in yolk and albumen weight when they consumed diets containing 1.1% Lys compared with the control group that consumed diets containing 0.95% Lys, whereas results of Costa et al (2008) showed that albumen, yolk and eggshell weight and their proportion did not change by increasing Lys levels, while Pinto et al (2003) reported a significant reduction in eggshell proportion as a result of increasing Lys levels from 0.890% to 1.300%.…”
Section: Egg Qualitymentioning
confidence: 99%
“…Jardim Filho et al (2010) reported that egg production, egg weight, and FCR improved by increasing Lys level from 0.60% to 0.80% for 20 wk in Hy-Line W-36 aged 25 wk, whereas Figueiredo et al (2012) observed that increasing Lys level from 0.675% to 0.879% in Hy-Line W-36 laying hens age 42 wk for 16 wk did not modulate egg production, but egg weight, egg mass, and FCR improved as a result of increasing Lys levels. Moreover, Kakhki et al (2016) reported that feeding Hy-Line W-36 from 32 to 40 wk of age diet containing 0.807% Lys improved egg production, egg weight, egg mass, and FCR compared with control group (0.657% Lys), whereas results of Souza et al (2014) in Hy-Line brown laying hens showed that egg production, egg weight, egg mass, and FCR did not improve by feeding them diets containing different levels of Lys (0.70%, 0.75%, 0.80%, 0.85%, or 0.95%) from 25 to 41 wk of age, while in Dekalb White laying hens, Silva et al (2015) found that increasing the Lys level from 0.64% to 0.91% from 32 to 48 wk of age had no effects on egg production or FCR, but the egg weight improved significantly. Additionally, results of Kumari et al (2016) showed that egg production, egg weight, egg mass, and FCR did not respond to increasing Lys level (from 0.60% to 0.7%) in laying hens diets that containing different levels of crude protein.…”
Section: Productive Performancementioning
confidence: 99%